2016
DOI: 10.20960/nh.804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grape juice consumption on antioxidant activity and interleukin-6 concentration in lactating rats

Abstract: ResumenIntroducción: este estudio evaluó el efecto del consumo de zumo de uva sobre la capacidad antioxidante y el nivel de interleucina-6 en sangre de ratas lactantes. Material y método: dieciocho ratas Wistar lactantes adultas se dividieron en dos grupos: grupo control (CG) y grupo de zumo de uva (GJU). La actividad antioxidante se determinó mediante el método de secuestro de radicales libres (DPPH) y la Capacidad de Absorción Radical de Oxígeno (ORAC) por 2,2-difenil-1-picrilhidrazil (DPPH), y la interleuci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The beverages produced by using grapes are a good opportunity for consumers who want to consume grapes all seasons (Coskun, 2017). Grape juice is a fresh and nutritious beverage containing minerals, vitamins and phenolics (Faria et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The beverages produced by using grapes are a good opportunity for consumers who want to consume grapes all seasons (Coskun, 2017). Grape juice is a fresh and nutritious beverage containing minerals, vitamins and phenolics (Faria et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fruit juice and fruits in general contain many antioxidants such as carotenoids, anthocyanins, and flavonoids, which counter oxidative stress and inflammation which as discussed previously, plays a significant role in COVID-19 progression [ 49 ]. One study has shown that grape juice can lower the concentration of IL-6 in rats, and naringin has been shown to inhibit SARS-CoV-2 infection in vitro [ 50 , 51 ]. Our results here regarding citric fruits is contradictory, other fruits (apple, pear, peach, banana) and fruit juices were associated with less disease severity here.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, study concluded that consumption of grape juice in the period of lactation increases the antioxidant capacity in lactating rats and appears capable to decrease the inflammatory activity. 1 Study was performed to evaluate the protection of organic and conventional purple grape juices in brain, liver, and plasma from adult Wistar rats against the oxidative damage induced through carbon tetrachloride (CCl(4)). Result revealed that in view of the treatment groups, it was noticed that in all tissues and plasma, CCl(4) treatment increased the lipid peroxidation levels.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Overall, study established that consumption of grape juice in the period of lactation increases the antioxidant capacity in lactating and seems proficient to decrease the inflammatory activity. 1 Red grape juice consumption increased the antioxidant capacity of plasma without affecting concentrations of uric acid or ascorbic acid. Furthermore, juice supplementation displayed decrease in LDL-cholesterol and apolipoprotein B-100 concentrations, while increasing the concentrations of HDL cholesterol and apolipoprotein A-I.…”
Section: Introductionmentioning
confidence: 95%